Fluorescence spectral study in grapes (Vitis Vinifera L.) Benitaka variety to different solid soluble values - Tinini, Rodolpho C. R. (2016)
The spectral images used as an alternative to the quality nondestructive evaluation, can contribute to improve monitoring and control of variables involved in partial dehydrated grapes for production of juice and/or inc.W with the product quality as goal. This studs aimed to differentiate Benitaka variety grapes with different concentrations of soluble solids using spectral image of fluorescence. The grape samples come from to Vale do So Francisco-State of Bahia; and W ere forwarded to the Laboratory of Atomic Interactions-Institute of Physics of So Carlos, University of Sao Paulo. The treatments consisted by two (Ti and T2) being TI-fresh grapes (12.54 +/-0.09 Brix), and T2-partial dehydrated grapes (in forced air oven at T=65 degrees C and RH=50%) (13.32 +/-0.08 Brix). The fluorescence image system used consists in a scientific CCD camera, lens system, a variable optical filter, and illumination system with LEDs (UV-405 urn). The wavelengths spectrum used in this study were between 480 to 750 nin. The spectral calibration occurred through a principal component analysis (PCA) in Matlab, wherein principal components which represent most the data were selected, separating T1 e T2. To select the best Wave length Was applied a linear regression forward a PCA model to image data. After the PCA implementation was possible to distinguish the different soluble solids values in grapes to Ti and T2, setting the best wavelengths were to 480; 493; 552; 568; 605; 645; 666; 690 and 715 nm. The applied technique can contribute to technological advancement in the non-destructive evaluation field and real-time in high added value products such as derivatives Viticulture. (C) 2016, IFAC (International Federation of Automatic Control) Hosting by Elsevier Ltd. All rights reserved.time in high added value products such as derivatives Viticulture. (C) 2016, IFAC (International Federation of Automatic Control) Hosting by Elsevier Ltd. All rights reserved.